2021
DOI: 10.3390/jrfm14050220
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Graphic Methods and the DEA in Predicting the Risk of Bankruptcy

Abstract: The paper deals with the issue of analyzing the financial failure of businesses. The aim was to select key performance indicators entering the DEA model. The research was carried out on a sample of 343 Slovak heat management companies. When addressing the research problem, we made use of multidimensional scaling (MDS) and principal component analysis (PCA), which pointed out the areas of financial health of companies that may predict their financial failure. The core of our interest and research was the data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This study employs a sophisticated methodology that combines established research approaches with tailored adaptations to assess the efficiency of economic support policies amid the COVID-19 pandemic, with a specific emphasis on their influence on supply chain dynamics. Essential methodologies are adapted from prior studies by [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…This study employs a sophisticated methodology that combines established research approaches with tailored adaptations to assess the efficiency of economic support policies amid the COVID-19 pandemic, with a specific emphasis on their influence on supply chain dynamics. Essential methodologies are adapted from prior studies by [34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…Sueyoshi and Goto (2009) applied Principal Component Analysis to reduce the number of financial factors in order to reduce the computational burden of the DEA-DA model. Stefko et al (2021) used Principal Component Analysis and Multidimensional Scaling when selecting inputs and outputs for DEA models. Huang et al (2015) selected variables for DEA models based on gray relational analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its main idea is to establish a new multi-dimensional coordinate plane, then to project the most variable information onto the axis, on the condition that the number of axes is fewer than the number of variables. Examples of a PCA integrated DEA can be found in Štefko et al ( 2021 ), Liang et al ( 2009 ), Premachandra et al ( 2009 ), Adler and Yazhemsky ( 2010 ), etc.. It has been shown that PCA can improve the discriminant power of the overall analysis (Adler & Yazhemsky, 2010 ).…”
Section: Data and Variable Selectionmentioning
confidence: 99%